Evaluating the effectiveness of e‐cigarettes compared with usual care for smoking cessation when offered to smokers at homeless centres: protocol for a multi‐centre cluster‐randomized controlled trial in Great Britain. (7th March 2022) - Cox, Sharon; Bauld, Linda; Brown, Rachel; Carlisle, Matthew; Ford, Allison; Hajek, Peter; Li, Jinshuo; Notley, Caitlin; Parrott, Steve; Pesola, Francesca; Robson, Deborah; Soar, Kirstie; et al.
Abstract: Background and aims: Smoking is extremely common among adults experiencing homelessness, but there is lack of evidence for treatment efficacy. E‐cigarettes are an effective quitting aid, but they have not been widely tested in smokers with complex health and social needs. Here we build upon our cluster feasibility trial and evaluate the offer of an e‐cigarette or usual care to smokers accessing a homeless centre. Design, Setting and Participants: Multi‐centre two‐arm cluster‐randomized controlled trial with mixed‐method embedded process and economic evaluation in homeless centres in England, Scotland and Wales. Adult smokers (18+ years; n = 480) accessing homeless centres and who are known to centre staff and willing to consent. Intervention and Comparator: Clusters ( n = 32) will be randomized to either an e‐cigarette starter pack with weekly allocations of nicotine containing e‐liquid for 4 weeks [choice of flavours (menthol, fruit and tobacco) and strengths 12 mg/ml and 18 mg/ml] or the usual care intervention, which comprises very brief advice and a leaflet signposting to the local stop smoking service. Measurements: The primary outcome is 24‐week sustained carbon monoxide‐validated smoking cessation (Russell Standard defined, intention‐to‐treat analysis). Secondary outcomes: (i) 50% smoking reduction (cigarettes per day) from baseline to 24 weeks; (ii) 7‐day point prevalence quit rates at 4‐, 12‐ and 24‐week follow‐up; (iii) changes in risky smoking practices (e.g. sharing cigarettes, smoking discarded cigarettes) from baseline to 4, 12 and 24 weeks; (iv) cost‐effectiveness of the intervention; and (v) fidelity of intervention implementation; mechanisms of change; contextual influences and sustainability. Conclusions: This is the first study, to our knowledge, to randomly assign smokers experiencing homelessness to an e‐cigarette and usual care intervention to measure smoking abstinence with embedded process and economic evaluations. If effective, its results will be used to inform the larger‐scale implementation of offering e‐cigarettes throughout homeless centres to aid smoking cessation.